2022
DOI: 10.1002/jsfa.12139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bio‐augmented Daqu on microbial community, aroma compounds and physicochemical parameters of fermented grains during the brewing of Chinese special‐flavor baijiu

Abstract: BACKGROUND Bio‐augmented Daqu is used to improve the microbial community and physicochemical parameters of fermented grains, thus affecting the flavor and quality of baijiu. This study investigated the effects of bio‐augmented Daqu inoculated with Aspergillus niger NCUF413.1 and Saccharomyces cerevisiae NCUF304.1 on the microbial community, aroma compounds, and physicochemical parameters of fermented grains during special‐flavor baijiu brewing. RESULTS Compared with the control group (CG), the utilization of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This was opposite to the bacterial genera composition of the high-temperature daqu with superior and normal grades [ 16 ]. Lactobacillus and Weissella , belonging to lactic acid bacteria, were the dominant genera in mature medium-temperature daqu [ 30 ] and contribute to the formation of acidity and flavor compounds [ 31 , 32 ], which is consistent with our findings. In contrast, Bacillus was dominant in N-NXDQ, while the abundances of Lactobacillus and Weissella decreased, which could be explained by the fact that Bacillus inhibited the growth of lactic acid bacteria [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…This was opposite to the bacterial genera composition of the high-temperature daqu with superior and normal grades [ 16 ]. Lactobacillus and Weissella , belonging to lactic acid bacteria, were the dominant genera in mature medium-temperature daqu [ 30 ] and contribute to the formation of acidity and flavor compounds [ 31 , 32 ], which is consistent with our findings. In contrast, Bacillus was dominant in N-NXDQ, while the abundances of Lactobacillus and Weissella decreased, which could be explained by the fact that Bacillus inhibited the growth of lactic acid bacteria [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in order to obtain more complex avors, Sesame, Herbal and Fuyu avor types of Baijiu use mixed Jiuqu (Mix) during the production process, that is, a combination of Daqu with Xiaoqu or Fuqu, so they have more complex microbial communities during fermentation, and certainly, their microbial communities were closely related to the Jiuqu used. The production of Jiuqu happens in an open atmosphere, meaning that the numbers, populations, and dominant microorganisms in different Jiuqu can vary signi cantly (Fu et al, 2023). The results of ANOVA on the classi cation of Baijiu based on fermentation starters showed that there was no signi cant difference in glycerol content in Baijiu using LD and XQ, while there were signi cant differences in glycerol content among Baijiu using HD, MD and Mix as fermentation staters with these two (Fig.…”
Section: Comparison Of Glycerol According To Different Fermentation S...mentioning
confidence: 94%
“…The quality of alcoholic products and their impact on human health have also always been widely concerned. 1,2 Flavour is one of the important attributes that affect the quality of alcoholic products. Among them, higher alcohols are aroma compounds that contribute greatly to the flavour of alcoholic products; their different types (phenylethyl alcohol, isoamyl alcohol, n-propanol, isobutanol etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic products, as a type of fermented product that is deeply loved by consumers around the world, have a long history and a wide variety of products (Chinese baijiu , beer, wine, whisky etc.). The quality of alcoholic products and their impact on human health have also always been widely concerned 1,2 . Flavour is one of the important attributes that affect the quality of alcoholic products.…”
Section: Introductionmentioning
confidence: 99%